Public Procurement and Sustainability - Delpiazzo Rodríguez, Carlos Enrique (2015)
Currently, we can say that the environment is one of the most important topics, being that its incidence is increasingly valued by society.In that sense, in this article we study the figure of sustainable procurement. In this regard, the author believes that it would imply a due balance between wealth creation and social welfare. Therefore, the figure study goes beyond the change of words, but involves a change inperspective that should be analyzed in the light of the principles governing the law.